Analysis Of Online Learning Implementation In Schools During The Covid-19 Pandemic - Aditya Hartini; M. Ihsan Ramadhani (Journal of Sustainable Development Science, 2022)
This study aims to apply online learning during the Covid-19 pandemic at SDN 1 Nusa Indah, Tanah Laut Regency. This type of research uses descriptive qualitative. This research was conducted in the Odd Semester of the 2021/2022 Academic Year. The subjects used were teachers and students of class V. The sampling technique used was purposive sampling. Data collection techniques used are interviews, and documentation to determine the process of implementing the learning carried out. Data collection instruments include interview guidelines, questionnaire sheets, and documentation. The data analysis technique uses data reduction (data reduction), data presentation (data display), and drawing conclusions. The results of this study are the implementation of the online learning process during the Covid 19 pandemic at SDN 1 Nusa Indah, Tanah Laut Regency in class V, students and teachers have basic facilities that support online learning, teachers are able to carry out learning well using learning media, strategies , learning methods and approaches that are adapted to students, but there are still many obstacles faced between students who are not focused on learning, cannot interact directly with teachers, network constraints, and limited quotas.